PENGARUH KOMPETENSI DOSEN DAN MOTIVASI BELAJAR MAHASISWA TERHADAP PRESTASI BELAJAR PADA FAKULTAS EKONOMI UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARI BANJARMASIN - Apriya Santi; Siti Mardah (Jurnal Ilmu Ekonomi dan Bisnis, 2022)
Abstract: This study was conducted to determine how much influence the competence of lecturers, student learning motivation on learning achievement both partially and simultaneously. Marketing Management with a sample of 38 students. Data obtained through questionnaires distributed to respondents and processed again using IBM's version of SPSS 22 software with Multiple Linear Regression test equipment. This research is a quantitative descriptive research, namely research that wants to know the relationship between independent variables and the dependent variable. The results showed that the variables X1 and X2 had a positive and significant effect on the Y variable. Likewise, the F test results showed that the X1 and X2 variables simultaneously had a positive effect on the Y variable.